From Verses to Sustainable Fishing: Quranic Foundations for Marine Natural Capital Conservation - Asma, Chaker (LPPM IAIN Kudus, 2026)
The relationship between Islamic principles and environmental sustainability has been extensively explored in contemporary scholarship, with numerous studies examining the Quran’s guidance on ecological stewardship and sustainable development. While existing literature has broadly addressed Islam’s ethical framework for sustainable development, this paper focuses specifically on marine resources and fisheries as a natural capital within Quranic teachings. By analyzing Quranic verses related to seas, aquatic life, and resource management, this study seeks to establish a theological foundation for sustainable fisheries discourse. This study investigates the Quranic basis for the concept of marine natural capital and its consequent implications for sustainable fisheries governance. The findings indicate a strong potential for alignment between public policy and the environmental ethics promoted in the Quran. This study's findings indicate that effective policy implementation hinges on two intrinsically linked elements: humanity's full embrace of its role as khalifa (steward) and the integration of a faith-inspired normative framework. This approach bridges divine revelation with contemporary sustainability challenges, offering Quranically grounded insights for marine conservation. By emphasizing the moral obligations of humans—particularly fishers—as key ecosystem decision-makers, this faith-based model reorients conservation from external regulation to internalized ethical duty.